Progressive Educational Practices and Environments in Sweden: Preparing Students to Live and Work in the Global Age - R. D. Nordgren (Arizona State University, 2015)
A multi-site case study of three Swedish schools examined the dimensions of trust, responsibility, shared power (democracy), and global workforce competence as required by a decade-old national education reforms. A key finding was the existence of progressive educational practices including constructivist epistemology, evidenced by the schools organizational structure, the instructional methods employed, and the various roles engaged in by the teachers, students, and administrators. These progressive practices and the mechanisms used to sustain them in one Swedish public school system may be conducive to effective preparation of workers and citizens for the post-industrial economy and to live in a participatory democracy.